(untitled) (Journal of Hama University, 2024)
The research aimed to study the most important variables (marketing difficulties) facing grapevine farmers in the village of Zaidel, and therefore the factors responsible for explaining the largest percentage of the total variance using factor analysis, through a questionnaire form, which included questions related to the difficulties related to grape marketing for the agricultural season 2021-2022, For a random sample of 375 farmers, and the results showed, using factor analysis using the basic components method and orthogonal rotation of the axes using the Varimix method, that there are nine factors with a potential root greater than the correct one for each of them, which together explained 60.27% of the total variance, and these factors are difficulties related to the nature of the product, Difficulties related to material costs, difficulties related to the marketing process explained 12.11%, 20.48%, 27% of the variance for each of them, respectively.